Luxembourg : Staff Report for the 2000 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Luxembourg's economic and fiscal performance has remained impressive. A proactive policy approach focused on institutional reforms will bolster the economy and public finances to growth reversals. A shift to a more diversified pension system should be a policy priority. Further income tax reforms are desirable. The management of the public sector's holdings of financial assets should be improved. An exceptionally favorable economic environment has blunted Luxembourg's labor market rigidities but reforms are needed. Maintaining effective banking supervision and governance should remain a priority of public policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet